KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI KONSENTRASI BELAJAR SISWA KELAS X MATERI PLSV DAN PTLSV - Tri Cici Franciska; Iwit Prihatin; Marhadi Saputro (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
This study aims to analyze "The Ability to Understand Mathematical Concepts in View of the Learning Concentration of Class X Students on the Material of One Variable Linear Equations and Inequalities at SMK Negeri 01 Sadaniang". The research method used in this research is descriptive method, with a special research study with a purpose to analyze data sharing phenomena that are the subject of research. Researchers provide statements in the form of structured questionnaires and tests structured data then analyzed qualitatively descriptive to find out the truth contained in the research location. Data obtained from the results of questionnaires, tests, and student interviews, the subjects in this study were students of class X Multimedia SMK Negeri 01 Sadaniang. The research results show that: students in the category of high learning concentration can meet the indicators ability to understand mathematical concepts, students in the medium learning concentration category fulfill some indicators of the ability to understand mathematical concepts, and students in the category of low learning concentration have not been able to meet the indicators of the ability to understand mathematical concepts